Evaluating the St. George's respiratory questionnaire in idiopathic pulmonary fibrosis: a systematic review with meta-analysis of psychometric properties using COSMIN - Rowida Mohamed; Yves Paul Vincent Mbous; Khalid M. Kamal; Traci J. LeMasters; Toni Marie Rudisill; Rahul G. Sangani; Sijin Wen; Virginia G. Scott; George A. Kelley (Springer, 2024)
Abstract Background The St. George's Respiratory Questionnaire (SGRQ) and its idiopathic pulmonary fibrosis (IPF) version (SGRQ-I) are widely used to assess health-related quality of life in IPF. However, the psychometric properties of these questionnaires in the IPF population have not been thoroughly evaluated. This systematic review assessed and summarized the available evidence on the psychometric properties of the SGRQ and SGRQ-I in IPF patients. Methods Seven electronic databases were searched to identify relevant studies. The eligibility criteria included full-text studies focusing on the psychometric properties of the SGRQ and SGRQ-I in patients with IPF. The risk of bias, criteria for good measurement properties, and strength of evidence were assessed based on the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). The inverse-variance heterogeneity (IVhet) model was used to pool results for construct validity. Results A total of 24 studies were included; 19 assessed the psychometric properties of the SGRQ, and seven evaluated the SGRQ-I. Structural validity was assessed in one study for the SGRQ-I. Most domains of the SGRQ and SGRQ-I, except for the symptom domain of the SGRQ, had acceptable internal consistency. Both questionnaires demonstrated adequate test-retest reliability, known-groups validity, and responsiveness. Regarding construct validity, there were moderate to strong correlations with respiratory-specific measures, yet weaker correlations were observed with pulmonary function tests. Interpretability analysis revealed minor floor and ceiling effects. Conclusion The SGRQ and SGRQ-I have the potential to capture essential dimensions of health-related quality of life (HRQoL) in IPF. However, further research should focus on ensuring that the items and domains of these questionnaires truly reflect the unique challenges and experiences faced by patients with IPF through content validity studies.